The implementations of green employee relations in supporting environmental performance at Hilton Bali Resort - Ni Putu Itha Mas Putri Dewi; I Ketut Astawa; Ni Luh Eka Armoni (Journal of Applied Sciences in Travel and Hospitality, 2023)
Hilton Bali Resort is one of the hotels implementing Green Employee Relations. Hilton Bali Resort is concerned with employee performance by providing various employee activities that impact environmental performance. However, until now, the implementation of green employee relations has yet to be fully implemented at Hilton Bali Resort. This research aims to analyze the implementation of green employee relations and to find out how green employee relations can support environmental performance at Hilton Bali Resort. This research uses a qualitative approach with data analysis techniques, the Miles and Huberman Interactive model, which consists of data reduction, data display, and conclusion drawing/verification. Collecting data is done by interviewing the Human Resources Manager and Learning and Development Manager, doing direct observation, and validating by documentation. There are three green employee relations practices that Hilton Bali Resort has implemented, and three green employee relations practices still need to be executed perfectly. Every function of green employee relations has aided environmental performance. All parts of green employee relations can support the planet indicator: involving green practices, introducing green whistleblowing and helplines, training union representatives, joint consultations in resolving environmental issues, providing sharing programs, and recognizing unions. The profit indicator also has yet to be assisted by all functions of green employee relations. The suggestion through this research is that Hilton Bali Resort can implement the other green employee relations practices that have not been fully implemented by Hilton Bali Resort, namely introducing green whistleblowing and helplines, joint consultations in resolving environmental issues, and recognizing the union as a key stakeholder.